Monastycyzm w świecie duchowości ponowoczesnej. Organizacja Morska zakonem religijnym Kościoła scjentologicznego - Anoszko, Sergiusz (Humaniora. Czasopismo Internetowe, 2021)
Article synthetically describes the history, assumptions and a short description of the Religious Order of the Scientology – Sea Organisation, which was founded in 1967, thirteen years after when in Los Angeles was registered the first institution of the Church of Scientology. The text of the article is based on three basic types of sources: literature, memoirs of former members of the order and the relationship of current active monks, the information from whom was received at query time research at the Ideal Orgs (headquarters) of the Church in Spain and Hungary in 2016. Apart from presenting the image of contemporary monasticism in terms of the Scientology also is explained the basic religious concepts, that relevant for this Ron Hubbard’s cult. The last part of the article is devoted to the symbolism of the Sea Org, which is really a reflection of the ideological assumptions that entity.